Forensic accounting 2 – fraud / Hari Ramulu Munusamy - Munusamy, Hari Ramulu (2003)
Forensic Accounting (1) introduced briefly FORENSIC AND INVESTIGATNE ACCOUNTING, the need for forensic accounting, definition of related terminologies, what forensic accountants do, typical approaches to forensic accounting assignment, characteristics of a forensic accountant, the litmus test and the seven deadly sins of fraud perpetrators. Forensic Accounting (2) deals with FRAUD. This issue is given substantial consideration, as forensic accounting often involves allegations of fraud. The article is not intended to be exhaustive consideration of the topic, but an endeavor to justify the essence and understanding of fraud